2021
DOI: 10.1186/s12958-021-00830-0
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of ellagic acid on di-(2-ethylhexyl) phthalate-induced testicular structural alterations, oxidative stress, inflammation and sperm damages in adult mice

Abstract: Background Phthalates such as di (2-ethylhexyl) phthalate (DEHP) are well known exogenous substances, disrupting reproductive system function and structure. The current research demonstrated the effect of ellagic acid (EA) on DEHP-induced testicular injury in mice. Methods Thirty-five healthy adult male mice were randomly divided to five groups; normal saline receiving group, DEHP (2 g/kg/day, dissolved in corn oil, p.o.) receiving group, DEHP (2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…39 In addition, some environmental pollutants and viruses induce poor semen quality through increasing levels of oxidative stress. [40][41][42] Additionally, antioxidant treatment has been shown to have a positive effect on semen quality. 43,44 Moreover, several antioxidant or oxidant compounds were found to alleviate oxidative damage in sperm caused by FA exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In addition, some environmental pollutants and viruses induce poor semen quality through increasing levels of oxidative stress. [40][41][42] Additionally, antioxidant treatment has been shown to have a positive effect on semen quality. 43,44 Moreover, several antioxidant or oxidant compounds were found to alleviate oxidative damage in sperm caused by FA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that exposure to FA might increase the level of oxidative stress, resulting in the tissue damage and inflammation . In addition, some environmental pollutants and viruses induce poor semen quality through increasing levels of oxidative stress . Additionally, antioxidant treatment has been shown to have a positive effect on semen quality .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TAC of the ethanolic extract was 46.72 ± 3.86 mg gallic acid equivalent per gram, while the standard drug, ascorbic acid displayed 69.84 ± 3.98 mg gallic acid equivalent per gram. It has been reported that different species of Euphorbia such as Euphorbia hirta Euphorbia wallichii, Euphorbia antisyphilitica possess strong antioxidant potential [44,45]. The antioxidant power of the ethanolic extract might be due to polyphenols such as catechol, syringic acid, gallic acid, ellagic acid, cinnamic acid and caffeic acid as confirmed from HPLC analysis.…”
Section: Antioxidant Activitymentioning
confidence: 83%
“…Similarly, once these stem cells enter the spermatogenic pathway and p-tyrosol, 48 beta-caryophyllene, 49 saponin 38 and a variety of other antioxidant compounds, administered alone or in combination. [50][51][52] The ability of commercial antioxidant formulations to resolve the testicular pathology associated with oxidative stress, generated either through the local application of heat or genetic inactivation of glutathione peroxidase 5 (one of the major antioxidant enzymes in the epididymis) has also been clearly demonstrated in animal models. 53 Detecting DNA damage in testicular germ cells is traditionally achieved via the histological examination of testicular biopsy material, which is a significant intervention.…”
Section: Dna Damage During Spermatogenesismentioning
confidence: 99%
“…As a result, both oxidative DNA damage and apoptosis‐related, nuclease‐induced DNA fragmentation are observed when the testes is under stress, whether this is chemically, 36–38 psychologically, 39 or surgically 40 induced or the result of exposures to excessive ionizing radiation 41 or heat 42 . Several studies indicate that the germ‐line DNA damage associated with such testicular stress may be alleviated with reagents designed to impede the oxidative damage process such as lactoferrin 36 mitochondrial permeability transition pore inhibitors, 40 curcumin, 43 dimethyl sulfoxide, 41 lutein, 44 vitamin C, 45 vitamin E and vitamin C in combination, 46 silymarin, 47 trigonelline, 42 melatonin, 42 p‐tyrosol, 48 beta‐caryophyllene, 49 saponin 38 and a variety of other antioxidant compounds, administered alone or in combination 50–52 . The ability of commercial antioxidant formulations to resolve the testicular pathology associated with oxidative stress, generated either through the local application of heat or genetic inactivation of glutathione peroxidase 5 (one of the major antioxidant enzymes in the epididymis) has also been clearly demonstrated in animal models 53 …”
Section: Introductionmentioning
confidence: 99%